Differences In Learning Outcomes Of Students Taught With Problem Based Learning Model Assisted By iSpring Suite 10 Media And Powerpoint On Chemical Equilibrium Material - Ayulia Annisa Nasution; Jasmidi Jasmidi (UNDIKMA, 2023)
This research aims to determine whether there are differences in student learning outcomes taught with the Problem Based Learning model assisted by iSpring Suite 10 media and PowerPoint on chemical equilibrium material. This research method uses quantitative research methods. This research was conducted at SMA Negeri 4 Medan, where the population in this study were all students of class XI IPA. The samples used in this study were two classes determined by the purposive sampling technique. The samples in this study were XI IPA 5 class as the first experimental class taught with the Problem Based Learning model assisted by iSpring Suite 10 media and XI IPA 7 class as the second experimental class taught with the Problem Based Learning model assisted by PowerPoint media. This research was conducted by research stages: 1) Giving a pretest, 2) The learning process, and 3) Giving a posttest. This study uses test instruments in the form of multiple choice questions as many as 20 questions that have met the requirements. The results of the research data analysis obtained the average student learning outcomes in experimental class I pretest value (44,16) and posttest value (82,08) with an average increase in learning outcomes of 69,47%, and the average student learning outcomes in experimental class II pretest value (43,88) and posttest value (76,81) with an average increase in learning outcomes of 61,28%. The average difference in student learning outcomes (posttest scores) of the two experimental classes was obtained by 5,278. Hypothesis testing was carried out with a two-party t-test and obtained sig. (0,04) < ∝ (0,05) so that the results show that Ha is accepted and H0 is rejected, which means that there is a difference in the average learning outcomes of students taught with iSpring Suite 10 media and PowerPoint on chemical equilibrium material.